2010
DOI: 10.5053/ekoloji.2010.759
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring of Trace Elements with Lichens in Samsun City, Turkey

Abstract: Lichens have been widely used in biomonitoring studies. In this study, Cd, Cu, Pb and Zn concentrations in some foliose and fruticose lichens which are found in Samsun were investigated and the differences among the species in terms of trace element concentrations and possible interactions among heavy metals were also examined. The results of the present study show that the study area is polluted by Pb and Cd. The cadmium contamination levels were also higher than those of the other elements. The highest Pb (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Some toxic elements (Al, As, Ba, Be, Cd, Pb, Hg, Os, Th, Va) affect soil pH and uptake of the nutrients from the soil, which influence growth and development on terrestrial flora (Vitorello et al 2005). In addition, dust pollution may affect photosynthesis, respiration, transpiration and allows the penetration of some toxic gaseous pollutants (Kinalioglu et al 2010). Today, it is obviously known that, some organisms called ''biomonitors'' have better ability of accumulating certain metals and/or toxic elements and they can be used by scientists for monitoring many trace elements in their environments (Akguc et al 2008;Yasar and Ozyigit 2009;Yasar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some toxic elements (Al, As, Ba, Be, Cd, Pb, Hg, Os, Th, Va) affect soil pH and uptake of the nutrients from the soil, which influence growth and development on terrestrial flora (Vitorello et al 2005). In addition, dust pollution may affect photosynthesis, respiration, transpiration and allows the penetration of some toxic gaseous pollutants (Kinalioglu et al 2010). Today, it is obviously known that, some organisms called ''biomonitors'' have better ability of accumulating certain metals and/or toxic elements and they can be used by scientists for monitoring many trace elements in their environments (Akguc et al 2008;Yasar and Ozyigit 2009;Yasar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Increased inputs of metals in the terrestrial and aquatic environments have led to large-scale pollution of the environment. Same as anthropogenic mobilization of trace metals into the biosphere (Baslar et al 2009;Kinalioglu et al 2010), mobilization of trace metals in the alteration areas is also an important process in the global geochemical cycling of these elements.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, several studies have shown that lichens are excellent bioindicators of air pollution (Addison and Puckett, 1980;Farner et al, 1992;Gries, 1996;Jeran et al, 2002;Nash and Gries, 2002;Gartner Lee et al, 2006;Kinalioglu et al, 2010), mainly due to their susceptibility to the deposition of airborne pollutants in the form of soluble salts and particles (Nimis et al, 2002). Lichens accumulate and retain macronutrients, trace elements and metal elements to concentrations that exceed their physiological requirements, tolerating high concen-trations of toxic pollutants.…”
Section: Introductionmentioning
confidence: 99%